DETERMINATION OF COBALT(II) WITH 1-NITROSO-2-NAPHTHOL IN MICELLAR MEDIUM BY FIRST DERIVATIVE SPECTROPHOTOMETRY - Shar, G. A.; Soomro, G. A. (The Nucleus, 2020)
A first derivative spectrophotometeric determination of cobalt(II) is carried out with 1-nitroso-2-naphthol as complexing reagent in aqueous phase using non-ionic surfactant Tween 40. The cobalt is determined in the range 1.7-120 ng mL-1 with detection limit (2Ïƒ) ï€ of 1.7 ng mL-1. The molar absorptivity and Sandell’s sensitivity are 1.86 ï‚´ 104 mol-1cm-1 and 3.6 ng cm-2 at 444.5 nm. The optimum pH of the complexation is 5. The critical micelle concentration (cmc) of Tween 40 is 5 %. Absorption studies in the first derivative mode is carried out to determine the absorption maximum of the complex for higher sensitivity and to overcome interferences. The present method is compared with that of AAS and no significant difference is noted between the two methods at 95 % confidence level. The method has been applied for the determination of Co(II) in pharmaceutical samples.